Dialectics of Fiqh al-Ikhtilāf: A Comparative Madhhab Analysis of Legal Pluralism in Contemporary Muslim Societies - Abu Baedah, Said Syarifuddin; Musolin, Mukhamad Hadi; Nurlaelah (Mazahibuna: Jurnal Perbandingan Mazhab, 2026)
Although the Islamic legal tradition recognizes diversity of opinion (ikhtilāf) as an integral, legitimate aspect of juristic reasoning, contemporary Muslim societies often face tensions when interpretive differences intersect with competing religious and sociopolitical authorities. Existing studies on fiqh al-ikhtilāf have largely remained within normative and descriptive discussions of classical legal theory and rarely examine how juristic diversity operates in contemporary social contexts. This article addresses this gap by examining ikhtilāf through a socio-legal and comparative madhhab perspective. The study employs qualitative, library-based research, combining textual analysis of classical jurisprudential sources from major Sunni madhhabs with socio-legal interpretation to explore how differences in legal reasoning are constructed, negotiated, and applied in contemporary Muslim discourse. The findings indicate that juristic disagreement arises not only from technical differences in linguistic interpretation or methods of istinbāṭ (legal derivation) but also from varying epistemological frameworks among madhhabs and their interaction with evolving social contexts and authority structures. Comparative analysis shows that classical madhhab traditions historically accommodated legal pluralism within a structured jurisprudential framework. In contrast, contemporary contestations often emerge when interpretive authority becomes fragmented. This article contributes to the sociology of Islamic law by proposing an ethical-jurisprudential framework grounded in fiqh al-ikhtilāf. The framework integrates madhhab diversity, legal pluralism, and ethical principles (akhlāq al-karīmah) as mechanisms for managing disagreement constructively. By reframing juristic diversity as an institutionalized form of legal pluralism rather than a source of division, the study highlights its potential role in strengthening social cohesion within contemporary Muslim societies.